Representasi Karakter Utama dalam Film My Idiot Brother 2014 - anhar, Anhar; Istikomah, Anggita; Ramadhani, Elisa; Zakiya, Nadhia Khoiri (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to analyze the emotional representation of characters with intellectual limitations in the film My Idiot Brother. This study uses a descriptive qualitative approach with the aim of describing the emotional meaning displayed by the characters in the film My Idiot Brother using a semiotic approach. The focus of the research is how the main character, Hendra, displays emotions such as anger, sadness, emotion, and happiness to convey a moral message about acceptance and empathy. Data is collected through repeated observation and documentation of cutouts of relevant scenes. Semiotic analysis is carried out to interpret the symbolic meaning of the expression of the character. The results indicate that the visualized emotions reflect social dynamics within a family with a member who has special needs, underscoring the importance of family support free from stigma. These findings demonstrate the role of film in shaping public perceptions of individuals with disabilities and fostering social inclusion. This study contributes to the discourse on character representation in media and promotes inclusivity